2015
DOI: 10.1039/c5ta03900b
|View full text |Cite
|
Sign up to set email alerts
|

MOF derived Co3O4nanoparticles embedded in N-doped mesoporous carbon layer/MWCNT hybrids: extraordinary bi-functional electrocatalysts for OER and ORR

Abstract: High efficient and non-precious metal electrocatalysts for oxygen evolution reactions (OER) and oxygen reduction reactions (ORR) are at the heart of key renewable-energy technologies. Nevertheless, developing highly-active bi-functional catalysts at low cost for both OER and ORR still remains a huge challenge. In this paper, Co3O4 nanocrystals embedded in N-doped mesoporous graphitic carbon layer/multiwalled carbon nanotubes (MWCNTs) hybrids are prepared by a facile carbonization and subsequent oxidation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
194
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(201 citation statements)
references
References 48 publications
7
194
0
Order By: Relevance
“…Therefore, it is of great significance to develop effectivec atalysts from earth-abundant materials. Hence,t ransition-metal/metal oxide nanoparticles andp orous carbon nanostructures have received considerable attention,d ue to their high chemical and thermals tability, and flexibility fort uning of the surfacea nd interface chemistry for the ORR, the OER, or bifunctionality.F or example, attempts have been made in the synthesis of heteroatom-doped carbon nanostructures (graphene, carbon nanotubes (CNTs), and carbon fibers), [6][7][8] metalorganic framework (MOF)-derived metal-NÀCs tructures, [9][10][11] perovskites, [12][13][14][15] and transition-metal oxides (TMOs). [16][17][18][19][20] TMOs, with their multiple oxidation states, show promising surfacea ffinities foro xygen catalysis;t he best examples are cobalto xides.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great significance to develop effectivec atalysts from earth-abundant materials. Hence,t ransition-metal/metal oxide nanoparticles andp orous carbon nanostructures have received considerable attention,d ue to their high chemical and thermals tability, and flexibility fort uning of the surfacea nd interface chemistry for the ORR, the OER, or bifunctionality.F or example, attempts have been made in the synthesis of heteroatom-doped carbon nanostructures (graphene, carbon nanotubes (CNTs), and carbon fibers), [6][7][8] metalorganic framework (MOF)-derived metal-NÀCs tructures, [9][10][11] perovskites, [12][13][14][15] and transition-metal oxides (TMOs). [16][17][18][19][20] TMOs, with their multiple oxidation states, show promising surfacea ffinities foro xygen catalysis;t he best examples are cobalto xides.…”
Section: Introductionmentioning
confidence: 99%
“…Here, J is the current density, J L and J K are the diffusion-and kinetic-limiting current densities, respectively, ω is the angular velocity, F is the Faraday constant (96,485 C mol −1 ), C 0 is the O 2 bulk concentration (C 0 = 1.26 × 10 −6 mol cm −3 ), D 0 is the diffusion coefficient of the O 2 in 0.1 M KOH or HClO 4 (D 0 = 1.9 × 10 −5 cm s −1 ), υ is the kinematic viscosity of the electrolyte (υ = 0.1 m 2 s −1 in 0.1 M KOH or HClO 4 ) [35].…”
Section: Resultsmentioning
confidence: 99%
“…Although the metal ions in MOFs are inclined to be reduced to metal NPs during carbonization, it is still likely to convert the metal ions into compounds directly by selecting appropriate precursors and controlling the annealing conditions. [36,42,43,45,73,74,76,[85][86][87][88][89][90][91][92][93][94][95][96][97][98] The most easily obtained compound is transition metal carbides due to the availability of carbon originating from the decomposition of organic ligands. [36,42,43,45,73,74,76,88,93] The case depicted in Figure 1b supports this point.…”
Section: Transition Metal Compounds Compositionmentioning
confidence: 99%
“…For instance, compositing MOF precursors with conductive supports, such as CNTs, [69,95] graphene, [33,34,92] and carbon fabric, [94] has been widely explored to enhance catalytic activity. Recently, Lai et al reported ZIF-8-derived N-enriched meso-microporous carbon (NEMC) frameworks.…”
Section: Structure Engineeringmentioning
confidence: 99%
See 1 more Smart Citation